Assembléia de aves em praças da área urbana da cidade de Santarém, PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Urbanization degrades natural environments, making green areas such as squares highly relevant for the conservation of biodiversity in cities. This study sought to characterize bird assemblages in five squares in the central area of the city of Santarém-PA and compare ecological parameters of these assemblages. Data collection was carried out through fixed transects between November 2020 and October 2021, with each square sampled monthly in the morning and afternoon periods. In total, I recorded 44 species belonging to 19 families. São Sebastião square had the highest number of species (n=39). The most representative guilds were insectivores, omnivores and granivores. There was no evidence of a significant relationship between species richness and the predictive variables (size of the square area, tree abundance and tree richness) and I found a high qualitative similarity of the registered species. Considering the richness of bird species that occurs in the region of Santarém, the results of this study demonstrate that the richness of birds in the squares sampled in the central area of Santarém is relatively low, possibly due to the high anthropization of the environment and the modified landscape. These results show the need to implement environmental policies aimed at maintaining areas such as squares and parks in urban environments in Santarém.
Keywords: Amazônia; Biodiversidade; Conservação; Ecossistemas Urbanos; CNPQ:: CIÊNCIAS BIOLÓGICAS